Added value of 18F-FDG PET/CT in diagnosing infected hip prosthesis. (May 2018) - Kwee, Robert M; Broos, Wouter AM; Brans, Boudewijn; Walenkamp, Geert HIM; Geurts, Jan; Weijers, René E
Background: The diagnosis of infected hip prosthesis is frequently not straightforward yet very important as it changes treatment. Purpose: To retrospectively investigate the added value of 18F-FDG PET/CT to conventional tests including radiography, erythrocyte sedimentation rate (ESR)/C-reactive protein (CRP) testing, and joint aspiration, in diagnosing infected hip prosthesis. Material and Methods: Seventy-eight hip prostheses of 78 patients (55% men; mean age = 66.5 years; age range = 30–85 years) with non-specific clinical presentation, i.e. no abscess or sinus tract communicating with the joint space at clinical examination, were analyzed. Cultures of intra-articular fluid and peri-implant tissues after revision surgery or clinical follow-up ≥6 months served as gold standard. Areas under the receiver operating characteristic curves (AUCs) of radiography, ESR/CRP testing, aspiration culture, and white blood cell (WBC) count without and with the addition of 18F-FDG PET/CT were compared. Results: The addition of 18F-FDG PET/CT increased AUCs: for radiography with 0.212, P  = 0.001; for ESR/CRP testing with 0.076, P  = 0.072; for aspiration culture with 0.126, P  = 0.032; and for aspiration WBC count with 0.191, P  = 0.035. Conclusion: This study shows that 18F-FDG PET/CT adds to individual conventional tests in diagnosing infected hip prosthesis. It may improve the preoperative planning and should therefore be considered in the diagnostic work-up. Future studies should define the exact place of 18F-FDG PET/CT in the diagnostic work-up of periprosthetic joint infection.